2021
DOI: 10.3389/fpsyg.2021.627934
|View full text |Cite
|
Sign up to set email alerts
|

Job Security and Organizational Citizenship Behaviors in Chinese Hybrid Employment Context: Organizational Identification Versus Psychological Contract Breach Perspective Differences Across Employment Status

Abstract: The goal of the present research was to identify the mechanism through which job security exerts its different effects on organizational citizenship behaviors (OCB) among contract and permanent employees from social identity and social exchange perspectives. Our research suggests two distinct, yet related explanatory mechanisms: organizational identification and psychological contract breach, to extend the job security literature by examining whether psychological contract breach and organization identity comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Therefore, when they perceive organizational betrayal repeatedly, they will be more likely to choose to leave, so there is little accumulation of their psychological contract breach experience within the same enterprise. In contrast, influenced by the idea of "Iron Rice Bowl (a lifelong secure job or position), " employees of state-owned enterprises are highly dependent on the organization itself (Lu et al, 2021(Lu et al, ). 10.3389/fpsyg.2022 Even the experience of psychological contract breach continues to increase, they will still not choose to leave, which may instead result in job burnout or a drop in job performance.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when they perceive organizational betrayal repeatedly, they will be more likely to choose to leave, so there is little accumulation of their psychological contract breach experience within the same enterprise. In contrast, influenced by the idea of "Iron Rice Bowl (a lifelong secure job or position), " employees of state-owned enterprises are highly dependent on the organization itself (Lu et al, 2021(Lu et al, ). 10.3389/fpsyg.2022 Even the experience of psychological contract breach continues to increase, they will still not choose to leave, which may instead result in job burnout or a drop in job performance.…”
Section: Discussionmentioning
confidence: 99%
“…Some considered psychological contract as an independent variable ( Alcover et al, 2017 ; Deng et al, 2018 ), while others consider organizational identification as an independent variable ( Hamzagić, 2018 ; Tufan and Wendt, 2020 ). At the same time, there had been more literature on the impact of psychological contract fulfillment or breach on employees’ psychological behavior ( Danilwan et al, 2020 ; Lu et al, 2021 ; Zhang et al, 2021 ), and less attention had been paid to the impact of various types of psychological contract on employees’ psychological behavior. This study find that different types of psychological contract had different effects to organizational identification, which provided an empirical basis for research on psychological contract.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, permanent employees have greater access to resources due to their more favorable status, which could benefit them in coping with job insecurity. Research has demonstrated that permanent employees work in core positions that are crucial to the organization's functioning; they mostly have a good working relationship with their supervisors and teammates as well (Lu et al, 2020). As such, permanent employees usually have more enriched cognitional and psychological resources to cope with job insecurity (Puig et al, 2008).…”
Section: Moderating Effect Of Employment Statusmentioning
confidence: 99%